Distribution and genetic diversity of Pseudocercospora SPP. associated with banana Sigatoka diseases in East Africa - Kimunye, Janet Njeri (Stellenbosch : Stellenbosch University, 2020)
Thesis (PhDFoodSc)--Stellenbosch University, 2020.